2013
DOI: 10.7182/pit2013817
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Analysis of Delayed Administration of Antithymocyte Globulin for Induction Therapy in Kidney Transplantation

Abstract: Patients who had delayed administration of rabbit antithymocyte globulin had shorter stays (3.9 vs 3.1 days, P< .001) and reduced inpatient costs for rabbit antithymocyte globulin (mean $860/patient); these changes were achieved without affecting acute rejection rates (5% vs 5%, P> .99) or readmission rates. In conclusion, delayed inpatient administration of rabbit antithymocyte globulin provided identical clinical outcomes while helping to reduce inpatient costs and increase timely discharges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…With short course treatment, there was a 30% cumulative dose reduction compared to standard treatment and no differences were reported in biopsy confirmed acute rejection or serum creatinine levels at 3 or 6 months post-transplant. Another cost saving measure was evaluated by McGillicuddy et al (16) They reported that delayed administration of final dose of rATG by administration in the outpatient setting on the day of discharge versus inpatient administration resulted in a cost savings of $860 per patient without affecting acute rejection rates or readmission rates. This could also result in a mean increase in revenue generation of approximately $1,856 per patient because the dose was administered in the institutions outpatient clinic.…”
Section: Induction Agentsmentioning
confidence: 99%
“…With short course treatment, there was a 30% cumulative dose reduction compared to standard treatment and no differences were reported in biopsy confirmed acute rejection or serum creatinine levels at 3 or 6 months post-transplant. Another cost saving measure was evaluated by McGillicuddy et al (16) They reported that delayed administration of final dose of rATG by administration in the outpatient setting on the day of discharge versus inpatient administration resulted in a cost savings of $860 per patient without affecting acute rejection rates or readmission rates. This could also result in a mean increase in revenue generation of approximately $1,856 per patient because the dose was administered in the institutions outpatient clinic.…”
Section: Induction Agentsmentioning
confidence: 99%
“…Previous studies have suggested depleting antibodies are the preferred agents for induction in patients at high risk for acute rejection, although definitions of “high risk” varied between studies . In addition, multiple studies have examined efforts to minimize the inpatient cost of induction therapy, the largest medication cost burden to the transplant postoperative stay …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In addition, multiple studies have examined efforts to minimize the inpatient cost of induction therapy, the largest medication cost burden to the transplant postoperative stay. 13,14 The increased risk of infectious complications associated with potent, lymphocyte-depleting induction prompted an early investigation at our center to compare depleting and nondepleting agents in otherwise low-immunological risk African American kidney transplant recipients. Despite a proposed association between African American race and poor graft outcomes, there were no differences observed in BPAR or graft loss based on induction agent.…”
Section: Introductionmentioning
confidence: 99%
“…By shifting doses of the induction therapy agent rabbit antithymocyte immune globulin from the inpatient to the outpatient setting, McGillicuddy et al 18 demonstrated a $230,867 improvement in net margin for 85 patients over a 14-month period, with no differences in clinical outcomes (delayed graft function, acute rejection, graft loss, or opportunistic infections) as compared with a historical control group. The same group of authors demonstrated significant cost savings by implementing a similar strategy (shifting the use of medications from the inpatient to the outpatient setting) with additional high-cost antibody medications, including basiliximab and rituximab.…”
mentioning
confidence: 97%
“…The same group of authors demonstrated significant cost savings by implementing a similar strategy (shifting the use of medications from the inpatient to the outpatient setting) with additional high-cost antibody medications, including basiliximab and rituximab. 18 Thus, antibody stewardship strategies to maximize the efficient use of high-cost antibody therapy can have profound effects on the net margins of transplantation centers and hospital systems.…”
mentioning
confidence: 99%